Living Dead in the Pacific : Contested Sovereignty and Racism in Genetic Research on Taiwan Aborigines - Munsterhjelm, Mark, 1966- (UBC Press, 2014)
Colonized since the 1600s, Taiwan is largely a nation of settlers. Yet within its population of 23 million are some 500,000 Aboriginal people. Genetic research has permeated both the political and popular spheres as Taiwanese nationalists and Chinese nationalists argue over the significance of migration theories and as the media proliferates genetic theories on predispositions to alcoholism. As this book demonstrates, genetics serve, on the one hand, to reinforce claims to a unique national identity and, on the other hand, to reinforce anti-Aboriginal prejudices. Increasingly, genetic research on Aborigines is being integrated into biotechnology planning, both in the country and through controversial US patent applications. The legacy of this work has been mass violations of the rights of Taiwanese Aborigines. Examining a troubling revival of racially configured genetic research and the questions of sovereignty it raises, Living Dead in the Pacific details a history of exploitation and resistance that represents a new area of conflict facing Aboriginal people both within Taiwan and around the world.